Constructal thinking: Geospatial and temporal focal points of activity - Baciu, Dan C.; Wolf, Lillian; Errera, Marcelo R.; de Oliveira, Vinicius Braz; Gunes, Umit (ELSEVIER SCI LTD, 2026)
The term constructal was brought into English usage by Adrian Bejan in 1996. Since then, it has spread across scientific communities, inspiring engineers and scientists, and helping them advance their research. At the constructal law conferences held in Turin, Bucharest, and Miami, we presented research results surveying how the term constructal has spread, reaching researchers and their laboratories around the world. As part of this research, we have observed that constructal thinking occurs in focal points of activity in both a geographical and historical sense. Geographically, there are centers of activity that emerge around universities, and historically, there are moments in time when the activity in these centers reaches its highest peaks. Here we discuss these observations, highlighting that they are expected in the study of human culture. In addition, we showcase that the constructal law has predicted similar phenomena in other fields. Hydrodynamics is one example.
Keywords: Constructal law; Text mining; Geospatial analysis; Historical analysis; Life Sciences & Biomedicine - Other Topics; Mathematical & Computational Biology